Molecular surveillance of norovirus, 2005–16: an epidemiological analysis of data collected from the NoroNet network. Issue 5 (May 2018) - van Beek, Janko; de Graaf, Miranda; Al-Hello, Haider; Allen, David J; Ambert-Balay, Katia; Botteldoorn, Nadine; Brytting, Mia; Buesa, Javier; Cabrerizo, Maria; Chan, Martin; Cloak, Fiona; Di Bartolo, Ilaria; et al.
Summary: Background: The development of a vaccine for norovirus requires a detailed understanding of global genetic diversity of noroviruses. We analysed their epidemiology and diversity using surveillance data from the NoroNet network . Methods: We included genetic sequences of norovirus specimens obtained from outbreak investigations and sporadic gastroenteritis cases between 2005 and 2016 in Europe, Asia, Oceania, and Africa. We genotyped norovirus sequences and analysed sequences that overlapped at open reading frame (ORF) 1 and ORF2. Additionally, we assessed the sampling date and country of origin of the first reported sequence to assess when and where novel drift variants originated. Findings: We analysed 16 635 norovirus sequences submitted between Jan 1, 2005, to Nov 17, 2016, of which 1372 (8·2%) sequences belonged to genotype GI, 15 256 (91·7%) to GII, and seven (<0·1%) to GIV.1. During this period, 26 different norovirus capsid genotypes circulated and 22 different recombinant genomes were found. GII.4 drift variants emerged with 2–3-year periodicity up to 2012, but not afterwards. Instead, the GII.4 Sydney capsid seems to persist through recombination, with a novel recombinant of GII.P16–GII.4 Sydney 2012 variant detected in 2014 in Germany (n=1) and the Netherlands (n=1), and again in 2016 in Japan (n=2), China (n=8), and the Netherlands (n=3). The novel GII.P17–GII.17, first reported in Asia in 2014, has circulated widely in Europe in 2015–16 (GII.P17 made up a highly variable proportion of all sequences in each country [median 11·3%, range 4·2–53·9], as did GII.17 [median 6·3%, range 0–44·5]). GII.4 viruses were more common in outbreaks in health-care settings (2239 [37·2%] of 6022 entries) compared with other genotypes (101 [12·5%] of 809 entries for GI and 263 [13·5%] of 1941 entries for GII non-GII.Pe–GII.4 or GII.P4–GII.4). Interpretation: Continuous changes in the global norovirus genetic diversity highlight the need for sustained global norovirus surveillance, including assessment of possible immune escape and evolution by recombination, to provide a full overview of norovirus epidemiology for future vaccine policy decisions. Funding: European Union's Horizon 2020 grant COMPARE, ZonMw TOP grant, the Virgo Consortium funded by the Dutch Government, and the Hungarian Scientific Research Fund.